The Implementation of Agile Project Management Using BIM Influences on the Construction Industry in The UAE Sector - DABASH, OMAR SALAH (2022)
This paper will explore the application of Agile project management principles in the construction industry using building information modelling (BIM) to examine the outcomes in the UAE industry sector by performing quantitative research. Certain principles of Agile project management and BIM which are highly related to the success of the construction projects were tested. Participants were asked to rate on a 5-point Likert scale how effective having an iterative process, flexibility, and collaborative culture which are the independent Agile variable factors being studied. Furthermore, participants were asked to rate their belief on how BIM can contribute to enhancing time management, resource management and waste reduction, which are the dependent variable factors being studied. A correlation is made between time, resource, and waste reduction with the agile factors in the UAE construction industry. It was found that applying Agile project management through the aid of BIM can have positive implications such as reducing projects’ duration cycle and enhance resource management and reducing waste in the UAE construction industry